Introduction to Polarization Physics - Nurushev, Sandibek B. (Lecture Notes in Physics,, 2013)
This book is devoted to the polarization (spin) physics of high energy particles and contains three parts. The first part presents the theoretical prefaces of polarization in the particle physics for interpretations, predictions and bases for understanding the following two parts. The second part of the book presents the description of the essential polarization experiments including the recent ones. This part is devoted to the innovative instrumentations, gives the parameters of the polarized beams, targets, polarized gas jets and polarimeters. The third part of the book concentrates on the important achievements in polarization physics. The book can be used in lectures on nuclear and particle physics and and nuclear instruments and methods. As supplementary reading this book is useful for researchers working in particle and nuclear physics.